An Ascetic and a Surasundari figures on the northern wall - Temples of India Project Team (Jio Institute, 2024)
There is another instance where an ascetic and a surasundari (celestial damsels) are shown next to each other. On the northern wall, the ascetic, now bereft of intricate details, reflects the simplicity and lack of materialistic wealth when juxtaposed with the jewellery-adorned surasundari. Though headless, she gleams with jewels. A slight flex of her posture graces her form with delicacy. Her full bosom is draped in lavish necklaces, one of which hangs down in between her breasts. A heavy girdle ornaments her slim waist, its loops descend gracefully down her legs. In her hand, she holds a kalasha (water pot) with flourishing tendrils, a testament to abundance and growth.